Firming non-political actors to enhance the quality of urban service delivery. A review on the City Development Forums in Uganda - Mwesigwa, David; Acanga, Alfred; Oryang, Alex Chono; Oboi, Alex (Goodwood Publishing, 2022)
Purpose: This study aimed to explore the dependability of non-political forums specifically considering the City Development Forums in Uganda. This investigation was motivated by the idea of City Development Forums being a known spectrum for Non-Political Forums to play a role in affairs otherwise affecting a City or Municipality. Research methodology: A Desk review method was adopted in which data was collected from obtainable resources specifically Publications, the Internet, Official Reports, etc., followed by cross-referencing and collation of data. Results: The outcomes reveal that a set of six principles inform City Development Forums, viz. shared accountability of every stakeholder in ensuring sustainable development; integrated planning framework for sustainable urban development; effective coordination among every urban stakeholder; local teamwork and networking; bottom-up broad-based stakeholder participatory consultations; and mobilization of resources for sustainable urban development. Limitations: This study adopted a review of secondary data yet if primary data were to be used, maybe, the results would have been different. Therefore, a different study can be conducted using primary data to determine whether these results hold sway and, if any, the justifications for the noticeable variances. Contribution: This study contributes to the understanding of local community development initiatives using the empowerment approach.